“Sack of marble” appearance in mature cystic teratoma: an unusual finding - Shrestha, Prajmi; Baral, Gehanath; Bhansakarya, Rakina; Chaudhary, Amar Nath (Nepal Journal of Obstetrics and Gynaecology, 2021)
Mature cystic teratoma (Dermoid) of ovary is a benign germ cell tumor consisting predominantly of ectodermal derivatives. In rare occasion sebaceous material may get aggregated to form marble like appearance because of continuous mobility of Dermoid and its content. Such a case in a menopausal woman has been presented in this report.